Synthesis and biological evaluation of S-lipidated lipopeptides of a connexin 43 channel inhibitory peptide. Issue 9 (10th July 2020) - Yang, Sung-Hyun; Clemett, Connor A.; Brimble, Margaret A.; O'Carroll, Simon J.; Harris, Paul W. R.
Abstract : Lipidated Peptide5 analogues are able to mediate hemichannel openings leading to inhibition of chemical messengers to the extracellular matrix. Abstract : The synthesis and biological activity of 42 novel S -lipidated analogues of a connexin 43 channel inhibitory Peptide5 is described. Unmodified Peptide5 moderates hemichannels and gap junctions that are both implicated in the progression of neurological disease. Peptide5 was site-specifically modified with a cysteine residue, which then underwent thiol–ene mediated S -lipidation to afford S -lipidated Peptide5 analogues containing straight-chain, branched, or aromatic lipids. The modified peptides were assessed for their effect on hemichannel opening and the most promising candidates were evaluated in serum stability studies.